Method for preparing iron monatomic catalyst

By preparing iron single atomic catalyst based on metal organic frame precursors, the problems of easy agglomeration of single atomic catalysts and slow kinetics of zinc air batteries are solved, and efficient and low-cost catalyst preparation and battery performance improvement are achieved.

CN120565696APending Publication Date: 2025-08-29UESTC (SHENZHEN) ADVANCED RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510728651.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

Existing single-atom catalysts are prone to agglomeration and inactivation, zinc-air batteries have slow kinetics, high cost of relying on precious metal catalysts, and insufficient activity stability of non-precious metal catalysts.

Method used

Iron single atom catalyst is prepared based on the metal organic framework precursor. By controlling the molar ratio of iron to zinc, adding dopamine hydrochloride to provide a nitrogen source and carbon source, calcining at high temperature under an inert atmosphere, forming a nitrogen-doped carbon matrix to stabilize iron single atoms.

Benefits of technology

The uniform dispersion of iron single atoms in the nitrogen-doped carbon matrix is ​​achieved, the density of ORR active site and the stability of the catalyst are improved, the cost is reduced, and the performance of zinc air batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120565696A_ABST
    Figure CN120565696A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst preparation, and discloses a method for preparing an iron monatomic catalyst, which comprises the following steps: 1, mixing zinc acetate dihydrate Zn (CH3COO) 2.2 H2O with water to form a first solution; 2, adding ferric nitrate Fe (NO3) 3 into the first solution, and uniformly stirring to form a zinc-iron-containing precursor solution; zinc-iron MOF is constructed through zinc acetate, ferric nitrate and dimethylimidazole, the nitrogen / carbon source effect of dopamine is combined, and high-dispersion F monatomic active sites are obtained through high-temperature calcination. According to the iron monatomic catalyst, in an acid environment (0.5 M H2SO4), the half-wave potential of an oxidation reduction reaction (ORR) is 0.83 V to 0.86 V (vs.RHE); in an alkaline environment (0.1 M KOH), the ORR half-wave potential ranges from 0.85 V to 0.90 V (vs.RHE); the electron transfer number is greater than or equal to 3.9, which indicates that the four-electron reaction path is dominant. When the material is used for a zinc-air battery, the peak power density reaches 221 mW / cm < 2 >, and the specific capacity is 790 mAh / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, in particular to a method for preparing an iron single-atom catalyst. Background Art

[0002] Single-atom catalysts have shown great potential in the field of catalysis due to their extremely high atomic utilization and unique electronic structure.

[0003] However, existing methods (such as impregnation and co-precipitation) often face problems such as metal atom agglomeration and uneven distribution of active sites. In addition, traditional calcination processes easily lead to deactivation of active sites. In addition, zinc-air batteries have attracted much attention due to their high energy density, low cost and environmental friendliness, but their cathode ORR kinetics are slow and they rely on precious metal catalysts (such as Pt / C), resulting in high costs. Existing non-precious metal catalysts (such as Fe-NC) are low-cost, but their activity and stability are insufficient. Summary of the Invention

[0004] (1) Technical problems solved

[0005] In response to the shortcomings of the existing technology, the present invention provides a method for preparing iron single-atom catalysts, which solves the problems that single-atom catalysts have potential but are easily agglomerated and deactivated, zinc-air batteries have slow ORR, rely on precious metal catalysts with high costs, and non-precious metal catalysts have insufficient activity and stability.

[0006] (2) Technical solution

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing an iron single-atom catalyst based on a metal-organic framework precursor, the preparation method comprising the following steps: step 1: mixing zinc acetate dihydrate Zn(CH3COO)2·2H2O with water to form a first solution; step 2: adding iron nitrate Fe(NO3)3 to the first solution and stirring evenly to form a zinc-iron precursor solution; step 3: mixing dimethylimidazole C4H6N2 and ammonia NH3·H2O to form a second solution; step 4: mixing the second solution with the zinc-iron precursor solution and adding dopamine hydrochloride C8H 11 NO2·HCl, stirring for 8h-12h to obtain a precipitate; step five: centrifuging, washing and drying the precipitate to obtain a precursor powder; step six: calcining the precursor powder at 900°C-1100°C for 1h-3h under inert gas protection to obtain an iron single-atom catalyst.

[0008] Preferably, the mass volume ratio of zinc acetate dihydrate to water in step 1 is 2.0g-2.5g:15mL.

[0009] Preferably, the amount of ferric nitrate added in step 2 is 5 mg-15 mg, and the molar ratio of iron to zinc is 1:100-1:500.

[0010] Preferably, the mass volume ratio of dimethylimidazole to ammonia water in step 3 is 1.5g-2.0g:20mL-25mL.

[0011] Preferably, the amount of dopamine hydrochloride added in step 4 is 20 mg-40 mg, and the stirring time is 8 h-12 h.

[0012] Preferably, the calcination temperature in step five is 950° C.-1050° C., and the inert gas is argon or nitrogen.

[0013] Preferably, the iron is dispersed in the nitrogen-doped carbon matrix in the form of single atoms.

[0014] Preferably, the iron single atom catalyst is mixed with a conductive agent and a binder, coated on a gas diffusion layer, and assembled into a zinc-air battery cathode, wherein the conductive agent is carbon black or carbon nanotubes, the binder is polytetrafluoroethylene (PTFE), and the catalyst loading is 0.5 mg / cm 2 -2.0mg / cm 2 The zinc-air battery electrolyte is a 6M KOH solution, and 0.2M Zn(OAc)2 is added as a zinc ion supplement.

[0015] Preferably, the iron single-atom catalyst has an ORR half-wave potential of 0.83V-0.86V in an acidic environment of 0.5M H2SO4; in an alkaline environment, such as 0.1M KOH, the ORR half-wave potential is 0.85V-0.90V; and the electron transfer number is ≥3.9, indicating that the four-electron reaction pathway is dominant.

[0016] (3) Beneficial effects

[0017] Compared with the prior art, the present invention provides a method for preparing an iron single-atom catalyst, which has the following beneficial effects:

[0018] 1. This method for preparing iron single-atom catalysts uses Zn-based MOF as a template, introduces an iron source through ferric nitrate, and utilizes MOF pores to restrict the migration of iron atoms and prevent agglomeration.

[0019] 2. In the method for preparing the iron single-atom catalyst, dopamine hydrochloride provides nitrogen and carbon sources during the high-temperature carbonization process, thereby enhancing the conductivity.

[0020] 3. This method for preparing iron single-atom catalysts involves high-temperature calcination under an inert atmosphere to induce the MOF skeleton to transform into a porous carbon matrix, while simultaneously achieving stable anchoring of iron single atoms.

[0021] 4. This method for preparing iron single-atom catalysts anchors iron in the nitrogen-doped carbon matrix in the form of single atoms, maximizing atomic utilization and providing high-density ORR active sites. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the preparation method of the present invention;

[0023] Figure 2 Schematic diagram of the SEM of the Fe single-atom catalyst of the present invention;

[0024] Figure 3 The high-angle annular dark field (HAADF) image and atomic-resolution HAADF image of the Fe single-atom catalyst of the present invention show the schematic diagram of the single-atom dispersion characteristics;

[0025] Figure 4 Schematic diagram of XRD of the Fe single atom catalyst of the present invention;

[0026] Figure 5 Schematic diagram for comparing the performance curves of the alkaline ORR polarization battery of the present invention;

[0027] Figure 6 Schematic diagram for comparing the performance curves of the acidic ORR polarization battery of the present invention;

[0028] Figure 7 Schematic diagram of the performance of the zinc-air battery of the present invention. DETAILED DESCRIPTION

[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0030] See also Figure 1-Figure 7 A method for preparing an iron single-atom catalyst based on a metal-organic framework precursor comprises the following steps:

[0031] Step 1: Mix zinc acetate dihydrate Zn(CH3COO)2·2H2O with water to form a first solution. This step is mainly to make the metal precursor dissolve evenly in the solvent, provide a uniform reaction basis, and ensure that the concentration of the solution can reach an ideal state in the subsequent reaction, laying a good foundation for the subsequent uniform dispersion of metal ions.

[0032] Step 2: Add ferric nitrate (Fe(NO₃)₃)₃ to the first solution and stir thoroughly to form a zinc-iron precursor solution. This process aims to ensure the coexistence of iron and zinc ions in the solution at a certain ratio, providing the necessary metal source for the formation of the metal-organic framework structure. Strictly controlling the molar ratio of iron to zinc is crucial for achieving single-atom dispersion, thereby preventing iron atoms from agglomerating in subsequent steps.

[0033] Step 3: Mix dimethylimidazole (C4H6N2) with ammonia (NH3·H2O) to form a second solution. This step primarily constructs the organic portion. Dimethylimidazole acts as an organic ligand to form a metal-organic framework, providing a precursor for the subsequent formation of the carbon matrix in the catalyst. Ammonia helps regulate the pH of the solution, promoting a uniform reaction.

[0034] Step 4: Mix the second solution with the zinc-iron precursor solution and add dopamine hydrochloride (C8H 11 The NO2·HCl mixture is stirred for 8-12 hours to produce a precipitate. During this stage, the components in the mixed solution interact with each other, forming a preliminary precursor precipitate. The addition of dopamine hydrochloride not only aids in the formation of the precipitate but also improves the structural properties of the precursor, ensuring good single-atom dispersion during the subsequent calcination process. Prolonging the stirring time promotes the full formation of the precipitate and the uniform distribution of the components.

[0035] Step 5: Centrifuge, wash and dry the precipitate to obtain a precursor powder. This step is to remove unreacted substances and solvent residues in the reaction system. The washing step generally uses multiple washes to ensure the purity of the precipitate. The drying process requires controlling the temperature and time to ensure the integrity of the precursor powder and its stability during the subsequent calcination process.

[0036] Step 6: Under inert gas, the precursor powder is calcined at 900-1100°C for 1-3 hours to produce the iron single-atom catalyst. During the calcination process, the organic matter carbonizes at high temperatures, while the metal ions react with the organic ligands to form a nitrogen-doped carbon matrix, into which the iron atoms are embedded as single atoms. The use of inert gas is to avoid oxidation reactions and maintain the single-atom state of the iron. Strict control of temperature and time is crucial to achieving the ideal catalyst structure and activity.

[0037] In step 1, the mass volume ratio of zinc acetate dihydrate to water is 2.0g-2.5g:15mL, the amount of ferric nitrate added in step 2 is 5mg-15mg, the molar ratio of iron to zinc is 1:100-1:500, and the mass volume ratio of dimethylimidazole to ammonia water in step 3 is 1.5g-2.0g:20mL-25mL. In step 4, the amount of dopamine hydrochloride added is 20mg-40mg, and the stirring time is 8h-12h. In step 5, the calcination temperature is 950℃-1050℃, and the inert gas is argon or nitrogen.

[0038] Mix 2.19 g of zinc acetate dihydrate with 15 mL of deionized water and stir until completely dissolved; add 10 mg of ferric nitrate and continue stirring for 30 minutes; mix 1.64 g of dimethylimidazole with 20.75 mL of ammonia water to form a transparent solution; slowly add the solution of step 3 to the solution of step 2, and then add 30 mg of dopamine hydrochloride, and stir at room temperature for 10 hours; collect the precipitate by centrifugation, wash it with ethanol three times, and dry it in a vacuum at 60°C for 12 hours; place the dry powder in a tubular furnace, heat it to 1000°C at 5°C / min under Ar atmosphere, calcine it for 2 hours, and naturally cool it to room temperature to obtain a black powdery iron single-atom catalyst with an iron element loading of approximately 0.32 wt%.

[0039] This experimental example details the specific amounts of each component and operating conditions to ensure reproducible operation. Throughout the entire experimental process, from dissolution to mixing, precipitate formation, and finally high-temperature calcination, each step is strictly controlled to ensure that the iron atoms are uniformly and stably dispersed within the nitrogen-doped carbon matrix in the final product.

[0040] Performance testing:

[0041] Acidic ORR: In 0.5 M H2SO4, the half-wave potential is 0.85 V and the Tafel slope is 50 mV / dec.

[0042] Alkaline ORR: In 0.1 M KOH, the half-wave potential is 0.88 V and the Tafel slope is 145.6 mV / dec.

[0043] These performance data indicate that the iron single-atom catalyst exhibits excellent redox activity across various pH conditions. The half-wave potential and Tafel slope, which reflect catalytic activity and reaction kinetics, respectively, are of great significance for practical electrochemical applications.

[0044] Application of iron single-atom catalysts prepared based on metal-organic framework precursors:

[0045] Iron is dispersed in the nitrogen-doped carbon matrix in the form of single atoms. The iron single atom catalyst is mixed with a conductive agent and a binder, coated on a gas diffusion layer, and assembled into a zinc-air battery cathode. The conductive agent is carbon black or carbon nanotubes, the binder is polytetrafluoroethylene (PTFE), and the catalyst loading is 0.5 mg / cm 2- 2.0mg / cm 2 The zinc-air battery electrolyte consists of a 6M KOH solution with 0.2M Zn(OAc)2 added as a zinc ion supplement. The iron single-atom catalyst exhibits an ORR half-wave potential of 0.83V-0.86V in an acidic environment (0.5M H2SO4) and 0.85V-0.90V in an alkaline environment (0.1M KOH). The electron transfer number is ≥3.9, indicating a dominant four-electron reaction pathway.

[0046] This application proposal details the configuration of the catalysts after assembly into the cathode and their matching with the battery system. Using carbon black or carbon nanotubes as conductive agents effectively improves the electron transfer efficiency of the electrode, while PTFE as a binder helps form a stable electrode structure. The loading amount, solution concentration, and additive ratio are optimized to ensure the ideal power density and specific capacity of the zinc-air battery in practical use.

[0047] When using:

[0048] Cathode slurry: catalyst, carbon nanotubes, and PTFE are mixed in a ratio of 7:2:1;

[0049] Assembled cell: 6M KOH electrolyte, zinc foil anode;

[0050] Performance: Peak power density 221mW / cm 2 , specific capacity 790mAh / g.

[0051] A properly formulated cathode slurry ensures good adhesion and conductivity between the catalyst and other components. The battery assembly process requires strict control of the layer structure and interface contact to achieve optimal electrochemical performance.

[0052] Characterization results:

[0053] HAADF-STEM: shows that iron is uniformly dispersed in the form of single atoms without nanoparticle aggregation.

[0054] Electrochemical testing revealed that the redox reaction (ORR) half-wave potential was 0.83V-0.86V (vs. RHE) in an acidic environment (0.5M H2SO4); 0.85V-0.90V (vs. RHE) in an alkaline environment (0.1M KOH). The electron transfer number was ≥3.9. This catalyst is suitable for integration into proton exchange membrane fuel cells (PEMFCs) and zinc-air batteries.

[0055] Characterization results further validated the catalyst's structure and activity. High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) clearly demonstrated the single-atom dispersion of the iron atoms, while electrochemical testing data confirmed its excellent performance in the actual ORR reaction, providing strong support for its application in various fuel cells and zinc-air batteries.

[0056] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply the existence of any such actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article, or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or device. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of other identical elements in the process, method, article, or device comprising the element.

Claims

1. A method for preparing an iron single-atom catalyst, characterized in that: The preparation method comprises the following steps: Step 1: mixing zinc acetate dihydrate Zn(CH3COO)2·2H2O with water to form a first solution; Step 2: adding iron nitrate Fe(NO3)3 to the first solution and stirring evenly to form a zinc-iron precursor solution; Step 3: Mix dimethylimidazole C4H6N2 and ammonia NH3·H2O to form a second solution; Step 4: Mix the second solution with the zinc-iron precursor solution and add dopamine hydrochloride (C8H 11 NO2·HCl, stir and react for 8h-12h to obtain a precipitate; Step 5: centrifuging, washing and drying the precipitate to obtain a precursor powder; Step 6: Under the protection of inert gas, calcining the precursor powder at 900° C.-1100° C. for 1 h-3 h to obtain an iron single atom catalyst.

2. The method for preparing an iron single-atom catalyst according to claim 1, wherein: The mass volume ratio of zinc acetate dihydrate to water in step 1 is 2.0g-2.5g:15mL.

3. The method for preparing an iron single-atom catalyst according to claim 1, wherein: The amount of ferric nitrate added in step 2 is 5 mg-15 mg, and the molar ratio of iron to zinc is 1:100-1:

500.

4. The method for preparing an iron single-atom catalyst according to claim 1, wherein: The mass volume ratio of dimethylimidazole to ammonia water in step 3 is 1.5g-2.0g:20mL-25mL.

5. The method for preparing an iron single-atom catalyst according to claim 1, wherein: In step 4, the amount of dopamine hydrochloride added is 20 mg-40 mg, and the stirring time is 8 h-12 h.

6. The method for preparing an iron single-atom catalyst according to claim 1, wherein: The calcination temperature in step 5 is 950° C.-1050° C., and the inert gas is argon or nitrogen.

7. The method for preparing an iron single-atom catalyst according to claim 1, wherein: The iron is dispersed in the nitrogen-doped carbon matrix in the form of single atoms.

8. The method for preparing an iron single-atom catalyst according to claim 1, wherein: The iron single atom catalyst is mixed with a conductive agent and a binder, coated on a gas diffusion layer, and assembled into a zinc-air battery cathode. The conductive agent is carbon black or carbon nanotubes, the binder is polytetrafluoroethylene (PTFE), and the catalyst loading is 0.5 mg / cm 2 -2.0mg / cm 2 The zinc-air battery electrolyte is a 6M KOH solution, and 0.2M Zn(OAc)2 is added as a zinc ion supplement.

9. The method for preparing an iron single-atom catalyst according to claim 1, wherein: The iron single atom catalyst has an ORR half-wave potential of 0.83V-0.86V in an acidic environment of 0.5M H2SO4; In an alkaline environment, such as 0.1 M KOH, the ORR half-wave potential is 0.85 V-0.90 V; the electron transfer number is ≥3.9.